An evaluation on growth performance and carcass characteristics of integration (oil palm plantation) and feedlot finished Bali cattle - Leo, Teik Kee; Leslie, Daphne Elena; Loo, Shu San; Ebrahimi, Mahdi; Aghwan, Zeiad Amjad Abdulrazzak; Panandam, Jothi Malar; Alimon, Abdul Razak; Karsani, Saiful Anuar; Sazili, Awis Qurni (Medwell Journals, 2012)
The objective of this study was to evaluate the differences in growth performance and carcass characteristics of Bali cattle subjected to oil palm integration and two different feedlot finishing systems (basal vs. high energy). Eighteen, 24-30 months old male Bali cattle were involved in this study. The animals were randomly allotted into 3 feeding groups: Integration (INT), (n = 6 animals), Feedlot A (FA) with basal energy (n = 6 animals) and Feedlot B (FB) with high energy (n = 6 animals). The animals assigned to the integration system were allowed to graze on the native forages and legumes available under the oil palm plantation. The basal energy diet consisted of 5 kg Palm Kernel Cake (PKC) pellets + ad libitum corn stover and the high energy diet which consisted of 5 kg Palm Kernel Cake (PKC) pellets + ad libitum corn stover + 400 g calcium soap of palm oil fatty acids (Megalac®, Volac International Limited, UK) were fed to the animals in FA and FB, respectively. The feeding trial was conducted for 120 consecutive days excluding 3 weeks of adaptation period. The present data suggest that some of the growth parameters and carcass traits in Bali cattle can be enhanced through the feedlot finishing system.